Analisis Faktor-Faktor yang Mempengaruhi Kinerja Kelompok Wanita Tani (KWT) dalam Program P2L (Pekarangan Pangan Lestari) - Anggraeni, Nia; Arsyad, Apendi; Masithoh, Siti (Universitas Djuanda, 2023)
This study aims to find out the characteristics of the Bogor City Peasant Women's Group (KWT), find out the level of performance of the Bogor City KWT, and find out the factors that affect the performance of the Bogor City KWT. This study was conducted in March - April 2022. This research was carried out in Bogor City, namely at KWT Berkah MBR-Katulampa Bogor Timur, KWT Karya Cilendek Bogor Barat, KWT Sereh Wangi Genteng Bogor Selatan, KWT Nusa Indah Tegal Gundil Bogor Utara, KWT Srikandi Tanah Sereal. The respondents in this study were 35 respondents. Data analysis uses descriptive analysis and multiple linear regression analysis with SPSS. The characteristics of respondents were seen from age, land area, land status, education level, experience, and membership period. The level of performance in this study by looking at the function of the farmer group (a medium / learning vehicle, cooperation vehicle, and business unit) is relatively high (average score is 55,76). Simultaneously or Test F together indicates that there is an influence with the value of F Calculate > F Table which is 121,979 > 2.53. The results of the T-test (Partial) variable X which influences the Variable Y (Performance) are X1 (Experience), X2 (Level of Education), and X4 (Counseling). A multiple linear regression equation is Y = 26,203 + 1,185 X1 + 0.110 X2 + 0.272 X3 + 0.885 X4 + 0.547 X5.